Justification of Universal Iron Supplementation for Infants 6-12 months in Regions with a High Prevalence of Thalassemia - Sinlapamongkolkul P. (2023)
Introduction: Many clinicians hesitate to adopt a universal infant iron supplementation program due to the risk of increased iron absorption for those with thalassemia. We aimed to determine thalassemia prevalence in 6- to 12-month-old infants, along with the iron status of those with and without thalassemia. Methods: We performed a cross-sectional descriptive study of infants attending the Well Baby Clinic at Thammasat University Hospital for routine checkups. Complete blood count, hemoglobin electrophoresis, iron parameters, and molecular genetics for common α- and β-thalassemia were evaluated. Results: Overall, 97 of 206 (47%) participants had thalassemia minor, the majority having Hb E traits. None had thalassemia intermedia or major. Familial history of anemia or thalassemia presented an increased risk of detecting thalassemia minor in offspring (OR 5.18; 95% CI 2.60-10.33, p=0.001). There were no statistical differences in transferrin saturation, serum ferritin and hepcidin between iron-replete infants with thalassemia minor and those without. However, one-third of infants with thalassemia minor (31/97) also had iron deficiency anemia (IDA), with a similar risk of having iron deficiency to infants without thalassemia. There was no hepcidin suppression in our infants with thalassemia minor as compared to controls. Conclusions: Both thalassemia and IDA are endemic to Southeast Asia. Infants with thalassemia minor, particularly with Hb E and α-thalassemia traits, are at risk of IDA. Our short-term universal iron supplementation program for 6- to 12-month-old infants does not appear to increase the risk of those with thalassemia minor developing iron overload in the future.